2014
DOI: 10.1007/s00423-014-1242-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of postoperative pancreatic fistula

Abstract: The high incidence of POPF was accompanied by a shift from operative to non-operative management. However, the current management strategy is driven by the patient's condition and local expertise and is generally based on poor evidence. A randomized trial showed that enteral nutrition is superior to total parenteral nutrition, and pooled data of randomized trials failed to show any advantage of somatostatin analogs for accelerating fistula closure. The choice of percutaneous versus endoscopic drainage of perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 54 publications
(75 reference statements)
0
54
0
1
Order By: Relevance
“…This type of diabetes tends to be difficult to control, leaving patients with a considerably elevated risk for severe hypoglycemia. 7,8,16 The main implication of these findings is that, when possible, catheter drainage should be the primary step in management of severe pancreatic fistula. Relaparotomy should be reserved for patients who are not candidates for a minimally invasive intervention or whose condition is progressively worsening with catheter drainage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of diabetes tends to be difficult to control, leaving patients with a considerably elevated risk for severe hypoglycemia. 7,8,16 The main implication of these findings is that, when possible, catheter drainage should be the primary step in management of severe pancreatic fistula. Relaparotomy should be reserved for patients who are not candidates for a minimally invasive intervention or whose condition is progressively worsening with catheter drainage.…”
Section: Discussionmentioning
confidence: 99%
“…6,10,11 However, other studies have shown that completion pancreatectomy can be performed with a relatively good outcome (ie, low mortality), and the investigators argue that, in patients needing relaparotomy, the operation should be performed as soon as possible. 3,8,12,13 Primary catheter drainage is a less invasive alternative to relaparotomy; it reduces tissue damage and the systemic inflammatory response otherwise induced by surgical stress in these already critically ill patients. 3,14 In another group of critically ill patients with pancreatic disease (infected necrotizing pancreatitis), standard treatment is now a minimally invasive step-up approach consisting of percutaneous catheter drainage as a first step to be followed by surgical intervention if patients do not improve clinically.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One (or two) 4 × 10 mm uted at drainages were placed behind the pancreatic and biliary anastomosis, and the postoperative secretion was routinely monitored with respect to amylase contents. A nutritional jejunostomy was placed 20 cm next to the last jejunal anastomosis and utilized from the second postoperative day [13].…”
Section: Surgerymentioning
confidence: 99%
“…Pancreatic fistulas occur in pancreatic tumors, pancreatitis and by blunt or penetrating abdominal trauma [33]. The necrotizing pancreatitis can develop into isolated collections, multiple abscesses and pseudocysts, requiring percutaneous drainage or surgical necrosectomy involving the infectious focus and assisting in faster recovery of the patient.…”
Section: Acs American College Of Surgeonsmentioning
confidence: 99%